2023
DOI: 10.1007/s00775-023-01988-1
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding of a Cys2His2-type zinc finger protein is enhanced by the interaction with DNA

Abstract: Zinc finger proteins specifically recognize DNA sequences and, therefore, play a crucial role in living organisms. In this study the Zn(II)-, and DNA-binding of 1MEY#, an artificial zinc finger protein consisting of three finger units was characterized by multiple methods. Fluorimetric, circular dichroism and isothermal calorimetric titrations were applied to determine the accurate stability constant of a zinc finger protein. Assuming that all three zinc finger subunits behave identically, the obtained thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…Furthermore, the secondary structures of the formed complexes were almost identical (Figure 2) (Scheme 1a). The Cd(II) binding affinity of 1MEY# was found to be the highest among the available literature data with Cys2His2 ZFPs (Table 1), although it was still ~1-2 logβ units lower than the Zn(II) binding under similar conditions (logβ Zn(II) = 12.2) [52]. The difference between the Zn(II) and Cd(II) binding affinity of CP1 and TFIIIA was reported to be 2.5 [33,38], while in case of the Ros87, it was only 1.2 logβ units [60].…”
Section: Interaction Of 1mey# Zinc Finger Protein With Cd(ii)mentioning
confidence: 77%
See 3 more Smart Citations
“…Furthermore, the secondary structures of the formed complexes were almost identical (Figure 2) (Scheme 1a). The Cd(II) binding affinity of 1MEY# was found to be the highest among the available literature data with Cys2His2 ZFPs (Table 1), although it was still ~1-2 logβ units lower than the Zn(II) binding under similar conditions (logβ Zn(II) = 12.2) [52]. The difference between the Zn(II) and Cd(II) binding affinity of CP1 and TFIIIA was reported to be 2.5 [33,38], while in case of the Ros87, it was only 1.2 logβ units [60].…”
Section: Interaction Of 1mey# Zinc Finger Protein With Cd(ii)mentioning
confidence: 77%
“…A gradual metal-ion exchange was observed in the mass spectra with the subsequent formation of Zn 2 Cd 1 and Zn 1 Cd 2 mixed complexes and the Cd 3 species upon an increase in the Cd(II) excess. Since previously we could not distinguish the Zn(II) binding ability of the three subunits of 1MEY# ZFP [52], the ZF units (1MEY# bs) were considered to be identical here as well. The evaluation of the fluorometric titrations revealed that the apparent stability constant of the Cd(II)-1MEY# bs complex is ~2 orders of magnitude lower than that of the Zn(II)-1MEY# bs, characterised by a logβ Zn(II)-1MEY#bs, pH 7.4 of 12.2 [52].…”
Section: Interaction Of 1mey# Zinc Finger Protein With Cd(ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the truncated S. aureus DNA ligase lacking OBD ( Figure 1E ; Han et al, 2009 ), the T. filiformi DNA ligase harbors the OBD, which is involved in DNA binding DNA. Besides to the OBD (domain 2), the zinc finger motif (subdomain 3a) and the HhH motif domain (subdomain 3b), which are all known to bind to nucleic acids ( Trasviña-Arenas et al, 2021 ; Hajdu et al, 2023 ), are present in the T. filiformi DNA ligase, demonstrating a unique organization and spatial arrangement of these domains. Additionally, the T. filiformi DNA ligase has a BRCT domain with much mobility in the open conformation, which might act as a gate to regulate DNA binding and release.…”
Section: Thermostable Dna Ligases From Hyperthermophilic Bacteriamentioning
confidence: 99%